GIS Based Mapping of Natural Tourism Objects and Supporting Facilities in Semarang City - Immanuel Adhi Yudhayono Sihombing; Edi Kurniawan (Universitas Lambung Mangkurat, 2026)
The tourism sector in Indonesia is a field with significant development potential. However, success in attracting visitors is influenced by various factors, particularly supporting facilities. The quality of tourism supporting facilities is a fundamental spatial element that determines a destination’s competitiveness,however, there are often disparities in their distribution within urban areas. This study aims to evaluate the condition of supporting facilities at natural tourist attractions in the city of Semarang using the 4A components (Attractions, Accessibility, Amenities, and Ancillary) and to analyze their spatial distribution patterns. The method used in this study is a descriptive spatial approach utilizing GIS tools by applying multi-radius buffer analysis techniques (500m, 1000m, and 1500m). The research results revealed a significant spatial interdependence between road accessibility hierarchy and the density of supporting facilities. Taman Lele Tourism Village is recorded as having the highest availability of facilities, with 10 supporting amenities; although this is the same as Curug Gondoriyo, it is superior in terms of accessibility, as it is directly connected to the Semarang-Kendal arterial road. Conversely, tourist attractions in outlying areas such as Dung Tungkul, Mec Tapak, and Curug Gondoriyo exhibit a decline in attraction quality and a lack of amenities due to accessibility barriers (local/narrow roads) as well as inactive or neglected institutional management. This reinforces the theory of urban-oriented tourism agglomeration, where facilities tend to concentrate along the city’s main economic corridors. This study contributes a spatial evaluation model for local governments in formulating policies for equitable tourism infrastructure to reduce service disparities between growth centers and the outlying areas of Semarang City.